2021
DOI: 10.1177/13591053211008225
|View full text |Cite
|
Sign up to set email alerts
|

Conscientiousness and perceived physical symptoms: Mediating effect of life events stress and moderating role of resting respiratory sinus arrhythmia

Abstract: This study investigated the possible psychophysiological links between conscientiousness and perceived physical symptoms by examining the mediating role of life events stress and the moderating role of resting respiratory sinus arrhythmia (RSA). Participants participated in the collection of questionnaire data and physiological data ( N = 396). Results showed life events stress mediated the association between conscientiousness and perceived physical symptoms, and the indirect effect was only significant among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…The path 4 represented "Internal Drive=>Task Value=>Learning beliefs". The path 1 and path 3 were not significant [15].…”
Section: Mediating Effectmentioning
confidence: 79%
“…The path 4 represented "Internal Drive=>Task Value=>Learning beliefs". The path 1 and path 3 were not significant [15].…”
Section: Mediating Effectmentioning
confidence: 79%
“…These findings replicated previous evidence that individuals with high conscientiousness reported more frequent positive affect, greater life satisfaction, and less frequent negative affect [ 12 , 14 , 16 ], revealing that conscientiousness is a robust and prospective predictor of subjective well-being. On the one hand, individuals high in conscientiousness are likely to be more effective at regulating negative affect [ 18 ] and may experience less daily stress [ 27 , 32 ]. On the other hand, individuals high in conscientiousness are more likely to be self-disciplined, goal-directed, industrious, and rule-abiding [ 4 ], and their efficient and reliable performance may promote success in school or the workplace [ 5 , 6 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conscientiousness was observed to be negatively associated with inflammation [ 22 ] and risks of chronic illness, such as sciatica, stroke, hypertension, and diabetes [ 23 , 24 , 25 ]. Accumulating evidence has consistently suggested that conscientiousness is a protective factor against physical health problems [ 26 , 27 , 28 ]. Recent findings from empirical studies have shown that individuals high in conscientiousness tend to report better physical health status [ 10 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%